Assesing the knowledge, perception, and attitude of wildlife management students toward biodiversity conservation in Nigeria (2023)
Despite intensified media campaigns and heightened emphasis on classroom instruction, recent international research has reported that young people are still failing to acknowledge biodiversity conservation as an issue of high priority. This study assessed students' knowledge, perception, and attitude toward biodiversity conservation in three Federal Universities offering Wildlife Management course in Southwestern Nigeria. A total of 159 respondents (15% sampling intensity) were surveyed using a structured questionnaire between July and December 2021. The findings revealed that most students had low knowledge of biodiversity conservation. This result is quite shocking given that they were enrolled in wildlife management courses. On the other hand, they had favorable attitudes and perceptions. The result further revealed that students in University of Ibadan had better attitude and perception. We concluded that there is a need to develop and teach programs and curricula that encourage and sustain the interests of wildlife students in biodiversity conservation.